Mengungkap Akuntabilitas dan Transparansi Pengelolaan Keuangan pada Pengelolaan Sumber Mata Air Pura Dalem Penyuratan di Banjar Badung Desa Bungkulan, Kecamatan Sawan, Kabupaten Buleleng - Komang Febrianty; Anantawikrama Tungga Atmadja (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This study aim at investigating regarding 1) the background for the formation of the Pura Dalem Penyuratan spring, and 2) How is the financial management system at the Pura Dalem Penyuratan spring. This research was conducted using qualitative methods. Data obtained through in-depth interviews, observation, and documentation study. The data is then analyzed by data reduction, data presentation, and drawing conclusions based on the predetermined theory. The results of this study indicate that: 1) The background for the establishment of the Pura Dalem Penyuratan spring is by asking for guidance from Ida Bhatara-Bhatari who is at Pura Dalem Penyuratan and is a common desire whose main goal is to further ease the economy of local residents, namely in terms of purchasing drinking water consumption, so that they do not have to buy drinking water in supermarkets, villagers can collect water from the spring at Pura Dalem Penyuratan voluntarily. 2) The financial management system of Pura Dalem Penyuratan spring water in the form of income and expenditure of money which will later be accumulated with money belonging to Pura Dalem Penyuratan and used for the benefit of springs and temples